Synthesis and Characterization of N,N-Dimethyl Aminophenyl Schiff’s Base-Chalcone Hybrid by In-silico and In-vitro Studies - Rajendran Nithyabalaji; Ramya Rajan M. P.; Rengarajan Kavitha (Current Research Progress in Physical Science Vol. 3, 2024)
The two biological active scaffolds (chalcone and Schiff base) were combined in a single compound by the simple synthetic methodology. Nuclear Magnetic Resonance (NMR), Fourier Transform – Infra Red (FT-IR), Ultraviolet (UV)-visible spectroscopy, and mass spectrophotometer techniques were used to characterize the synthesised compound. The reactivity of these compounds was theoretically revealed using Density Functional Theory (DFT) calculations such as Frontier Molecular Orbital (FMO), Mullikan charge distribution and molecular electrostatic potential (MEP) mapping studies by the use of Density Functional Theory (DFT) calculations, such as Frontier Molecular Orbital (FMO), Mullikan charge distribution, and molecular electrostatic potential (MEP) mapping studies, was revealed the reactivity of these compounds theoretically. Furthermore, the enzymes such as 1PGG.pdb, 4COX.pdb, and 1HNY.pdb which cause inflammation and diabetes were also carried out by molecular docking studies. In addition to that in-vitro activity of the inflammation and diabetes was also executed and results were compared with standard drug molecules. Schiff base ligands and their metal complexes have a wide range of applications reported so far. These complete theoretical and experimental studies could provide more functional details of the compounds in the wide applications of biological studies.